How Job Satisfaction Mediating the Influence of Non-Physical Work Environment and Career Development on Employee Turnover Intention at PT XYZ - Masruroh Masruroh; Sesilia Vanessa Audelia; Silvia Fransisca Tanto; Laksmi Sito Dwi Irvianti (Indonesia Banking School, 2020)
The purpose of this study was to determine the effect of the non-physical work environment as well as ca-reer development on job satisfaction and its impact on turnover intention at PT. XYZ. This research is quantitative, using path analysis research tools and survey research methods to collect primary data by dis-tributing questionnaires to 171 employees of PT. XYZ as the respondent. The results of the study indicate that there is a significant influence of the non-physical work environment and career development on turn-over intention, which is mediated by job satisfaction at PT. XYZ. A pleasant non-physical work environ-ment and the implementation of career development programs can reduce the level of turnover intention of employees of PT. XYZ, which is supported by the feeling of getting job satisfaction in completing tasks and responsibilities within the company. The implication of the results of this study is that PT. XYZ needs to improve human relationships both vertically and horizontally, design career planning programs, and design attractive financial and non-financial benefits plans.